Cooperative Learning Model Broken Triangle, Square, and Heart: Enhancing Student Engagement and Academic Performance in History Education at the Senior High School Level - I Ketut Arya Sentana Mahartha; Zulkarnain Zulkarnain (AL-ISHLAH: Jurnal Pendidikan, 2023)
Learning models have a significant role in fostering an active, collaborative, and engaging learning environment for students, which is essential for improving academic success in high school history instruction. It is intended that by actively engaging students in the learning process through an efficient learning paradigm, they will become more engaged and make more progress in comprehending and mastering historical content. Through the use of the cooperative learning model Broken Triangle, Square, and Heart, this project seeks to increase the interest and academic performance of high school students in their study of history. A pretest-posttest control group design was used in conjunction with an experimental study methodology. There were 72 students that made up the participants, and they were split into the experimental group and the control group. The choice of study participants was made at random. The distribution of questionnaires served as the method of data gathering. With the aid of SPSS version 25.0, statistical techniques were used to examine the data. The findings of the descriptive statistical analysis showed that both groups' academic achievement and interest levels had increased from the pretest to the posttest. The results of the ANOVA test showed a significant difference between the experimental and control groups' academic performance. The Broken Triangle, Square, and Heart cooperative learning model exposed students in the experimental group to larger improvements in interest and academic accomplishment than did students in the control group, according to the findings of the N-Gain test. The use of the cooperative learning model Broken Triangle, Square, and Heart is successful in boosting the enthusiasm and academic accomplishment of high school students in their study of history, according to the study's findings. The findings of this study have significant educational ramifications and highlight the need to create instructional strategies that actively engage studentss.